1999
DOI: 10.1182/blood.v94.10.3340.422k19_3340_3348
|View full text |Cite
|
Sign up to set email alerts
|

Responses in Refractory Hairy Cell Leukemia to a Recombinant Immunotoxin

Abstract: We report major responses in 4 of 4 patients with hairy cell leukemia (HCL) who have recently been treated on a phase I trial with the recombinant immunotoxin LMB-2. The immunotoxin, designed to target CD25+ malignancies, is composed of the Fv portion of the anti-Tac (anti-CD25) antibody, fused to a 38-kD truncated form of Pseudomonas exotoxin A, and has previously been called anti-Tac(Fv)-PE38. All 4 HCL patients were resistant to standard and salvage therapies for HCL, including 2-chlorodeoxyadenosine (CdA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(36 citation statements)
references
References 45 publications
0
34
0
1
Order By: Relevance
“…The chimeric anti-CD20 antibody, rituximab, has been shown to induce complete remission in a significant portion of patients with relapsed and newly diagnosed HCL [9]. Recombinant immunotoxin conjugated antibodies directed against CD25 and CD22 have been shown to be effective in patients with HCL with chemotherapy-resistant disease [7,8]. The demonstration of CD52 on HCL cells offers an additional therapeutic target for treatment of refractory HCL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chimeric anti-CD20 antibody, rituximab, has been shown to induce complete remission in a significant portion of patients with relapsed and newly diagnosed HCL [9]. Recombinant immunotoxin conjugated antibodies directed against CD25 and CD22 have been shown to be effective in patients with HCL with chemotherapy-resistant disease [7,8]. The demonstration of CD52 on HCL cells offers an additional therapeutic target for treatment of refractory HCL.…”
Section: Resultsmentioning
confidence: 99%
“…Still, cases of HCL leukemia refractory to standard therapy occur, and effective alternatives are limited. Antibody therapy directed against antigens expressed on the neoplastic hairy cells might offer a salvage strategy for patients who have failed purine nucleoside analogues [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the immunogenicity of immunotoxins containing bacterial toxins can be reduced by the methods described above, and although their systemic toxicities can be controlled by clinical management (Kreitman et al, 1999), these immunotoxins have not yet been well accepted by the clinical community. This may change in the future, if two of the advanced agents using bacterial toxins, a CD22-scFv-ETA protein (Kreitman et al, 2001) and the fusion of a truncated diphtheria toxin and IL-3 (Testa et al, 2005), which are currently in clinical testing, should receive drug approval.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotoxins have great potential for selective cell depletion in a variety of clinical settings including cancer, graft vs. host disease, autoimmune disorders, allograft rejection, and viral infections. Such bifunctional proteins have received the greatest attention for rational design of anti-cancer therapeutics [18 -20]; indeed recent Phase I clinical trials have reported major responses against several hematologic malignancies [37][38][39][40][41], including many complete remissions in cases of chemotherapy-resistant hairy cell leukemia. Moreover, a conceptually related agent (Mylotarg) consisting of a cytoxic antibiotic chemically coupled to a recombinant monoclonal antibody has been approved for treatment of relapsing acute myelocytic leukemia in individuals over 60 years of age who are not considered candidates for cytotoxic chemotherapy [42].…”
Section: Discussionmentioning
confidence: 99%